Influence of family caregiver education level with their expressed emotion in caring for the elderly: (Study at the Surabaya community health center) - Anindya Arum Cempaka (Poltekkes Kemenkes Kupang, 2021)
Objective: The higher the level of education of a person, the wider the horizons of his thinking, so it is very helpful when a person grapples with stressful life events and develops coping skills to deal with stress. The stress faced by the caregiver will affect and increase expressed emotion. Caregivers with high expressed emotion are at risk of causing family members of person they cared for to experience stress. Methods: This is an observational analytic study with a cross-sectional design. A total of 56 family caregiver at Surabaya Community Health Centre participated in this study. The measuring instrument used is a sociodemographic questionnaire and a Family Questionnaire (FQ) assessing expressed emotion. Results: Statistical analysis generated a significant p-value of 0.000 with alpha of 0.05, thus the p-value ≤ 0.05. It indicated a significant association between education level with the expressed emotion of caregiver. Conclusion: The education level of the family of caregiver will affect their expressed emotion.